Kinerja perekonomian daerah dan kesejahteraan masyarakat di Daerah Istimewa Yogyakarta Tahun 2016-2020 - Rizki Hamdani; Elsye Mayshelly (Proceeding of National Conference on Accounting & Finance, 2023)
This study aims to examine the effect of economic capacity, budget governance, and financial performance on people's welfare. In addition, this study also identifies the effect of budget allocation on economic capacity. This research was conducted in the Province of the Special Region of Yogyakarta (DIY), which consists of four districts and one city. The data used in this study is secondary data originating from the website of BPS DIY Province and DJPK Ministry of Finance. The analytical method used is multiple regression analysis with the help of SmartPLS to examine and process data. Based on the results of hypothesis testing, it is known that economic capacity, budget management, and financial performance have a significant effect on people's welfare. In addition, budget allocation has a significant effect on economic capacity.